Pharmaceutical pharmacology - Mehta, S. C.; Kar, Ashutosh (New Delhi, 2009)
This title includes chapters that commence with a crisp introduction related to the 'subject matter' under discussion, followed by classification, treatment of each 'class of drugs' with reference to important 'drugs' vis-a-vis pharmacological actions, pharmacokinetic actions, mechanism of action, therapeutic uses, dosage regimens, adverse drug reactions, and drug interaction, wherever necessary. The text has been profusely substantiated with labeled diagrams, graphics, and lucid explanations. It gives to the reader an explicit route starting from a molecular understanding of receptors and drug activities to the therapeutic applications of the most import 'class of drugs'.
Keywords: PHARMACOLOGY